18F-DOPA Uptake of Developmental Venous Anomalies in Children With Brain Tumors. (July 2016) - Morana, Giovanni; Piccardo, Arnoldo; Garrè, Maria Luisa; Cabria, Manlio; Rossi, Andrea
Abstract : Abstract: We report the finding of increased 18 F-3, 4-dihydroxyphenylalanine uptake of the brain parenchyma adjacent to developmental venous anomalies, incidentally discovered in 3 pediatric patients with diffusely infiltrating gliomas. One patient presented 3 developmental venous anomalies located distant from the tumor, whereas in the remaining 2 patients, the vascular anomalies were inside the tumoral area mimicking a focal area of increased tumor metabolism. In the setting of brain tumor imaging, focal increased 18 F-3, 4-dihydroxyphenylalanine uptake should be carefully interpreted in light of MRI findings, and nuclear medicine physicians should be aware of any incidental minor vascular abnormality for proper interpretation of PET data.